Gerakan Koin Siswa sebagai Model Pembiayaan Pendidikan Berbasis Partisipasi Siswa di SMP Negeri 3 Kalimanah - Sa'diyah Handayani; Umi Kharisoh; Anang Kurnia Wahab; Muh. Hanif; Sudiro (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Education funding is one of the key factors in ensuring the continuity of educational services in schools. Limited funding sources often prompt schools to develop alternative funding strategies that involve the participation of the school community. This study aims to describe and analyze a student-participation-based education funding model through the Student Coin Movement at SMP Negeri 3 Kalimanah. The study employs a qualitative approach using a case study design. Data were collected through interviews with the school principal, the teacher in charge of the student coin program, the student council president, and students, and were supported by documentation regarding the management and utilization of funds. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The research results indicate that the Student Coin Movement is a voluntary fundraising program of Rp. 500–Rp. 1,000 per student per day, managed participatively by students, teachers, and the school association. The collected funds serve as a contingency fund to support the payment of guest teachers’ honoraria when Community Participation funds are not yet available. The program’s success is supported by a culture of participation established as early as elementary school, the voluntary nature of the program, the modest contribution amount, and the benefits directly felt by the school community. This study developed a student participation based education financing model that integrates student participation, school management, and community support to ensure the sustainability of education financing. The model demonstrates that collective student participation can serve as an effective and sustainable alternative funding source for schools.